PERSEPSI ORANG TUA TERHADAP 7 KEBIASAAN ANAK INDONESIA HEBAT DALAM MENDUKUNG PRESTASI OLAHRAGA SISWA - Rizky, Muhammad; Mashud, Mashud; Haffyandi, Recky Ahmad (Universitas Hamzanwadi, 2025)
This study aims to examine parents' perceptions of the 7 Great Habits of Indonesian Children (7KAIH) program in the context of character development and student athletic achievement. The research method employs a qualitative descriptive approach. The target population for this study consists of parents of students at SDN 3 Syamsuddin Noor whose children actively participate in sports activities and are already familiar with the 7KAIH program. The sample size for this study is 10 parents. Data analysis techniques include data reduction, data presentation, and drawing conclusions/verification. Data collection techniques were conducted through interviews and observations. Through the qualitative descriptive approach, data was collected through semi-structured interviews with ten parents of students at SDN 3 Syamsuddin Noor whose children are actively involved in sports activities. The results of the study indicate that some parents believe the 7KAIH program has a positive impact on children's independence, discipline, enthusiasm, and self-confidence in sports. Parents also play an important role in providing facilities, motivating, and accompanying children in developing their sports potential. However, there are still some obstacles, such as children's study time and social skills, which need to be improved. The conclusion of this study is that it has a positive influence on the development of children's attitudes, particularly regarding independence, discipline, enthusiasm, and self-confidence when they participate in sports activities. Support from parents, such as providing sports equipment and emotional encouragement, makes children more serious about training and participating in competitions.